Nepenthes barcelonae (Nepenthaceae), a new species from Luzon, Philippines - Cheek, Martin; Tandang, Danilo N.; Pelser, Pieter B. (Phytotaxa, 2015)
Nepenthes barcelonae is described as a new species in sect. Insignes, where it is unique in the inset mouth and the dichromic upper pitchers (first-produced pitchers red, later-produced pitchers green) which are also dimorphic. This is a newly recorded phenomenon in the genus: the first produced (primary upper pitchers) are red, larger, stouter, and have an uncoiled long tendril, while those later produced (secondary upper pitchers) are green, smaller, more slender, and have a coiled tendril. The only population of this species that is currently known grows in an area less than 10km² on a single mountain. Individual plants are at risk from collecting for the horticultural trade. Following the IUCN criteria, N. barcelonae is assessed as Critically Endangered.